Dukungan Budaya Ternate Terhadap Perawatan Luka Perineum Pada Ibu Nifas di Kelurahan Dorpedu Kecamatan Pulau Ternate (Studi Kualitatif) - Muhammad, Sinta; Ibrahum, Irma; Rahayu, Siti Nenden; Ati, Sarmina (Jurnal Ilmiah Wahana Pendidikan, 2025)
Perineal infection is a common problem after childbirth. Most of the people of North Maluku, especially the Ternate community, have a culture or tradition in treating lacerations in the perineal area. This study aims to describe the forms and patterns of culture in treating postpartum premium wounds in Dorpedu Village, Ternate Island District. This research is important to do in order to add information and references about the richness of culture or traditions in the form of traditional medicine that are spread throughout Indonesia. This study uses a qualitative approach. A qualitative approach is used because this approach can describe data or conditions in the field specifically. Data collection was carried out using in-depth interviews and observations on groups of informants and key informants. The research instrument is to use a voice recorder that has previously obtained approval from the informant. Sampling in this study is the principle of appropriateness and adequacy. Triangulation of sources to obtain the same information from different informants, while triangulation of methods to obtain data in several ways, namely through in-depth interviews and observations. The results of this study are the culture of the Dorpedu community in treating postpartum mothers is by using traditional medicine, namely drinking rorano or special concoctions from plants, barahu and bafufu. Mothers who have experienced postpartum believe in using medicine based on local culture.